DEVELOPMENT PROSPECTS OF TOURISM VILLAGES IN KASHKADARYA REGION - Yarashev Quvondiq Safarovich; Yusupov Baxriddin Bobonazarovich (Journals Park Publishing, 2023)
In the article, some aspects of the development of rural tourism in the Kashkadarya region, especially the natural and territorial conditions, were studied, and rural tourism is directly related to how the interaction between nature and man takes place. about the processes that took place. In our country, there are many places where tourists can relax and get healthy. Therefore, information was given about the fact that the mountainous and mountainous areas are unopened reserves for foreign tourists and their aspects in tourism.
Keywords: Mountains, countryside, ecotourism, waterfalls, forests, rivers, caves, lakes.